2023
DOI: 10.1186/s12877-023-04066-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise and physical activity on gut microbiota composition and function in older adults: a systematic review

Abstract: Background The characterization and research around the gut microbiome in older people emphasize microbial populations change considerably by losing the diversity of species. Then, this review aims to determine if there is any effect on the gut microbiota of adults older than 65 that starts an exercise intervention or improves physical activity level. Also, this review describes the changes in composition, diversity, and function of the gut microbiota of older subjects that had improved their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“… 39 In older adults specifically, physical activity-based interventions can cause an increase in health-related taxa but do not impact broad diversity measures. 43 …”
Section: Adult Microbiomementioning
confidence: 99%
“… 39 In older adults specifically, physical activity-based interventions can cause an increase in health-related taxa but do not impact broad diversity measures. 43 …”
Section: Adult Microbiomementioning
confidence: 99%
“…Obese individuals tend to have greater improvements in metabolic parameters associated with obesity (insulin tolerance, plasma triglycerides, and body fat distribution) after dietary intervention. A recent review from 2023 showed in almost all the cross-sectional studies that physical activity alone does not exert significant chang­es in gut microbiota diversity [4], but a combined intervention of exercise and nutrition could be useful to improve physical performance [5] and maintain an efficient microbiome.…”
Section: Knowledge Transfer Of şTefănescu Camelia-florina (Bucharest)mentioning
confidence: 99%
“…A large body of evidence supports the role of exercise in effectively preventing and treating chronic diseases such as obesity, hypertension, depression, diabetes, respiratory diseases, and cardiovascular diseases [11]. As these diseases have also been associated with specific GM composition and function [12], exercise may be more closely related to intestinal flora than previously thought.…”
Section: Introductionmentioning
confidence: 99%